(untitled) (Medicine Today, 2022)
Introduction: Urinary tract infection (UTI) is one of the common bacterial infections encountered by clinicians in clinical practice. Distribution and susceptibility of UTI-causing pathogens change according to time and place. Area-specific studies to gain knowledge about the type of pathogens and their resistance patterns may help the clinician to choose the proper antimicrobials for empirical treatment. Objective: This study was conducted to determine the distribution and antimicrobial susceptibility of uropathogens. Materials and Methods: This study was conducted in the Enam Medical College & Hospital, savar, Dhaka between January 2021 to June 2021 to identify the organisms causing UTI and their antibiotic susceptibility. Clean catch midstream urine samples were collected from 476 clinically suspected UTI patients and tested bacteriologically using standard procedures. Antimicrobial susceptibility test was performed by Kirby-Bauer disk diffusion method. Results: The prevalence of UTI was higher in females than in males. Out of the 170 culture positive bacterial isolates Escherichia coli was the most common 51.76% organism, followed by Staphylococcus aureus 28.82%, Staphylococcus saprophyticus 11.17%, Klebsiellaspp 8.23 % and Enterococcusspp 4.70%. Meropenem (100%) followed by Imipenem (92.86% to 100%) were found most susceptible drugs. While Trimethoprim-sulfamethoxazole and Cephradine were the most resistant drug against the isolated uropathogens. Conclusion: As bacterial drug resistance is an evolving process, routine surveillance and monitoring studies should be conducted to provide physicians knowledge on the updated and most effective empirical treatment of UTIs. Medicine Today 2022 Vol.34(1): 51-56